A Proposed Framework for Practicing Creative Thinking Skills in Teaching Science to Primary School Students in the Kingdom of Saudi Arabia - Al-Nufaie, Nasser Qutaym (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to identify the creative thinking skills necessary for teaching science to elementary students, explore methods for fostering these skills, and present a proposed framework for their classroom application. The researcher adopted a descriptive analytical approach and developed a list of creative thinking skills, validated by 18 experts for the skills and 14 for the enhancement methods.The main tool was a skill checklist, and the study sample consisted of the science textbook for the sixth grade in Saudi Arabia.The results revealed 35 sub-skills essential for teaching science creatively, distributed as follows: fluency (13 skills), flexibility (13), and originality (9). Additionally, 15 methods were identified to foster these skills, and a conceptual model was presented for implementing creative thinking in science education. Based on the findings, the study recommended preparing a supportive school environment, embedding creative-thinking content and strategies into science curricula, and training science teachers to adopt creative teaching practices. It also proposed further evaluations of science textbooks in light of these skills.
Keywords: Creative thinking; science education; elementary stage; teaching skills; classroom environment